Envisioning the future for families running away from war: Challenges and resources of Ukrainian parents in Italy - Paoletti, Patrizio; Perasso, Giulia Federica; Lillo, Carmela; Serantoni, Grazia; Maculan, Alessandro; Vianello, Francesca; Di Giuseppe, Tania (Frontiers in Psychology, 2023)
Since February 2022, 7.8 million people have left Ukraine. Eighty percent are women and children. The present quali-quantitative study is the first in Italy to: (i) describe the adaptation challenges and the resources of refugee parents and, indirectly, of their children; (ii) investigate the impact of a neuropsychopedagogical training on their well-being. The sample includes N=15 Ukrainian parents (80% mothers, mean age=34 years) who arrived in Italy in March and April 2022. The parents participated in a neuropsychopedagogical training within the program Envisioning the Future (EF): The 10 Keys to Resilience. Before the training, participants completed an ad-hoc checklist to detect adjustment difficulties. After the training, they responded to a three-item post-training questionnaire on the course, and to a semi-structured interview deepening adaptation problems, personal resources, and the neuropsychopedagogical training effects. Participants report that since they departed from Ukraine they have experienced sleep, mood, and concentration problems, and specific fears, which they also observed in their children. They report self-efficacy, self-esteem, social support, spirituality, and common humanity as their principal resources. As effects of the training, they report an increased sense of security, quality of sleep, and more frequent positive thoughts. The interviews also reveal a threefold positive effect of the training (e.g., behavioral, emotional-relational, cognitive-narrative).